Consumer attitudes to upcycled foods in US and China. (15th February 2023) - Grasso, Simona; Fu, Rao; Goodman-Smith, Francesca; Lalor, Fiona; Crofton, Emily
Abstract: A trend has emerged seeking to transform edible food waste into new consumable products, a process known as upcycling. However, there are limited studies on consumer knowledge and attitudes towards upcycled foods. This study is the first to compare a Western (United States (US)) and Eastern (China) country, in terms of consumer attitudes to upcycled foods and consumer preferences on new upcycled food combinations. The survey was distributed online and statistical analyses were performed to calculate differences between the two countries relating to willingness to try (WTT), willingness to buy (WTB), liking, familiarity, attractiveness, purchase likelihood and previous knowledge of upcycled foods. Results indicate that more participants in China had heard previously of upcycled foods than in the US, however familiarity was low in both countries. Overall, liking towards upcycled foods was higher in the USA than in China. In the US, the most popular combinations were snack foods with upcycled spent grains and upcycled vegetables included in soups, followed by upcycled fruit in snacks. In China the most popular combinations were fruit in snacks, breakfast foods and drinks. The preferred by-products in both countries were plant-based, but dairy was the third preferred choice in China. Chinese participants characterised upcycled foods in terms of quality and health more than the US, while 'reducing food waste' and being 'good for the environment' were equally associated with upcycled foods in both countries.